Signatures of unresolved binaries in stellar spectra: implications for spectral fitting. Issue 4 (26th October 2017) - El-Badry, Kareem; Rix, Hans-Walter; Ting, Yuan-Sen; Weisz, Daniel R.; Bergemann, Maria; Cargile, Phillip; Conroy, Charlie; Eilers, Anna-Christina
Abstract: The observable spectrum of an unresolved binary star system is a superposition of two single-star spectra. Even without a detectable velocity offset between the two stellar components, the combined spectrum of a binary system is in general different from that of either component, and fitting it with single-star models may yield inaccurate stellar parameters and abundances. We perform simple experiments with synthetic spectra to investigate the effect of unresolved main-sequence binaries on spectral fitting, modelling spectra similar to those collected by the APOGEE, GALAH and LAMOST surveys. We find that fitting unresolved binaries with single-star models introduces systematic biases in the derived stellar parameters and abundances that are modest but certainly not negligible, with typical systematic errors of 300 K in T eff, 0.1 dex in log  g and 0.1 dex in [Fe/H] for APOGEE-like spectra of solar-type stars. These biases are smaller for spectra at optical wavelengths than in the near-infrared. We show that biases can be corrected by fitting spectra with a binary model, which adds only two labels to the fit and includes single-star models as a special case. Our model provides a promising new method to constrain the Galactic binary population, including systems with single-epoch spectra and no detectable velocity offset between the two stars.